Stalking, harassment, gendered abuse, and violence towards politicians in the COVID-19 pandemic and recovery era - Every-Palmer, Susanna; Hansby, Oliver; Barry-Walsh, Justin (Frontiers in Psychiatry, 2024)
Background: High levels of harassment and threats against parliamentarians are being reported internationally, especially in the social media space. This is occurring alongside changes in our social landscape, with increasing political polarisation and the ongoing ramifications from the COVID-19 pandemic. Harassment of politicians has been shown to have implications for psychological wellbeing and physical safety.Objectives: To investigate harassment and violence towards parliamentarians in the COVID-19 pandemic and recovery era, including whether there had been a change in its nature and quantity, and to explore the contribution of social media.A survey of all New Zealand's parliamentarians was fielded in 2022, focusing on their experiences of harassment analysed quantitatively and with manifest and latent content analysis of free text responses. Data were disaggregated and compared by gender. Secondary analyses were conducted on similar data collected from parliamentarians in 2014 to compare trends over time.We obtained a cleaned achieved survey sample of 54 Members of Parliament (MPs). Harassment was reported by 98% of respondents, ranging from disturbing communication to actual physical violence. The vast majority of MPs endorsed multiple modalities of harassment occurring on multiple occasions. Ninety-six percent of MPs had been harassed over social media, with over half being threatened, including threats of physical violence (40%), sexual violence (14%), threats made towards MP's family members (19%), threats towards staff (12%), and death threats (27%). Almost all forms of harassment had increased significantly since 2014. Most MPs reported experiencing abuse related to the Government response to the COVID-19 pandemic (e.g. lockdowns and vaccine mandates). Many MPs commented that the frequency and intensity of abuse increased markedly during the COVID pandemic and had not subsequently abated. Women were at significantly higher risk of certain types of social media harassment including gendered abuse, sexualised comments, threat of sexual violence, and threats toward their family.Harassment of parliamentarians is an escalating issue. Online threats and misogyny are increasingly apparent. This harassment has significant psychosocial costs for victims, their family and staff, and for democratic processes.